Should the Mediterranean diet be recommended for inflammatory bowel diseases patients? A narrative review - Ratajczak, Alicja Ewa; Festa, Stefano; Aratari, Annalisa; Papi, Claudio; Dobrowolska, Agnieszka; Krela-Kaźmierczak, Iwona (Frontiers in Nutrition, 2023)
Inflammatory bowel disease (IBD) are chronic, progressive and relapsing inflammatory disorders of unknown aetiology that may cause disability over time. Data from epidemiologic studies suggest, that dietary factors may play a role in the risk of developing and course of IBD. It is known that the group of beneficial bacteria was reduced in the IBD and that the Mediterranean diet (MD)- which is defined as eating habits characterised by high consumption of cereals, vegetables, fruit, olive oil, and small portions of dairy products, pastry, sugar and meat products- affects gut microbiota, enriching beneficial bacteria, which support gut barrier function and reduce inflammation. Although several studies support different favourable effects of MD on IBD, adherence of MD by IBD patients is generally low, including patients from the Mediterranean Basin. Patients avoid many products, which are elements of MD, because there cause gastrointestinal symptoms. Patients should be encouraged to have a healthy and balanced diet according to individual tolerance of products. Good option seems to be good modified MD, changing hard to digest products on easy digest.